2013
DOI: 10.1038/sc.2013.19
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenic detrusor overactivity in adults: a review on efficacy, tolerability and safety of oral antimuscarinics

Abstract: Objectives: This review analyzed efficacy, tolerability and safety of oral antimuscarinic (AM) drugs in adults suffering from neurogenic detrusor overactivity (NDO). Methods: A comprehensive search of major literature bases was conducted to identify all references. Results: Thirty studies, thereof 16 randomized controlled trials (RCT), enrolling 1479 patients were identified and included in the review. Results were grouped in dose-finding, placebo-and active-controlled, flexible dose and combined high-dose AM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 35 publications
1
49
0
4
Order By: Relevance
“…9,10 In a review examining the results of 30 studies performed with a total of 1,479 patients with neurogenic detrussor overactivity, it was shown that antimuscarinic drugs (most commonly studied drugs; oxybutynin HCl, trospium chloride and propiverine) are effective after 2-3 weeks of therapy. 11 We also observed a significant increase in mean bladder capacity in our patients with SCI who had been put on 6/day IC and oral anticholinergic therapy for an overactive or hypocompliant detrusor. A retrospective study evaluating the effectiveness of anticholinergic drugs within a mean duration of 1 month (21-46 days) in 231 patients with overactive Table 2 Comparison of pre and post-treatment maximum cystometric capacities…”
Section: Discussionmentioning
confidence: 60%
“…9,10 In a review examining the results of 30 studies performed with a total of 1,479 patients with neurogenic detrussor overactivity, it was shown that antimuscarinic drugs (most commonly studied drugs; oxybutynin HCl, trospium chloride and propiverine) are effective after 2-3 weeks of therapy. 11 We also observed a significant increase in mean bladder capacity in our patients with SCI who had been put on 6/day IC and oral anticholinergic therapy for an overactive or hypocompliant detrusor. A retrospective study evaluating the effectiveness of anticholinergic drugs within a mean duration of 1 month (21-46 days) in 231 patients with overactive Table 2 Comparison of pre and post-treatment maximum cystometric capacities…”
Section: Discussionmentioning
confidence: 60%
“…These agents normalize intravesical pressure and increase cystometric bladder capacity. 55 They significantly reduce maximum detrusor pressure; however, reduction in detrusor overactivity persists only while the patient remains on the treatment. In addition, antimuscarinics are associated with several commonly noted adverse effects, particularly dry mouth and constipation, which can interfere with patient adherence to treatment.…”
Section: Second-line Optionsmentioning
confidence: 99%
“…Studies have demonstrated efficacy of at least 4 of them (oxybutynin, trospium chloride, tolterodine, darifenacin) in this patient population. 9,32,55,65 The detrusor muscle contains beta-adrenoceptors. Human bladder and urothelium contain beta1-, beta2-, and beta3-adrenoceptors 66 ; 97% of beta adrenoceptors in the human bladder are beta3.…”
Section: Second-line Optionsmentioning
confidence: 99%
“…The latter include antimuscarinic drugs [85] and botulinum toxin [86]. Nowadays, in developed countries, the life span of most SCI patients is long and approaches that of the general population.…”
Section: Accepted Manuscriptmentioning
confidence: 99%